Genome-Wide Characterization of the Methyl CpG Binding Domain-Containing Proteins in Watermelon and Functional Analysis of Their Roles in Disease Resistance Through Ectopic Overexpression in Arabidopsis thaliana - Liang, Jiayu; Li, Xiaodan; Wen, Ya; Wu, Xinyi; Wang, Hui; Li, Dayong; Song, Fengming (Frontiers in Plant Science, 2022)
Methyl-CPG-Binding Domain (MBD) proteins play important roles in plant growth, development, and stress responses. The present study characterized the MBD families in watermelon and other cucurbit plants regarding the gene numbers and structures, phylogenetic and syntenic relationships, evolution events, and conserved domain organization of the MBD proteins. The watermelon ClMBD proteins were found to be localized in nucleus, and ClMBD2 and ClMBD3 interacted with ClIDM2 and ClIDM3. ClMBD2 bound to DNA harboring methylated CG sites but not to DNA with methylated CHG and CHH sites in vitro. The ClMBD genes exhibited distinct expression patterns in watermelon plants after SA and MeJA treatment and after infection by fungal pathogens Fusarium oxysporum f.sp. niveum and Didymella bryoniae. Overexpression of CMBD2, ClMBD3 or ClMBD5 in Arabidopsis resulted in attenuated resistance against Botrytis cinerea, accompanied by down-regulated expression of AtPDF1.2 and increased accumulation of H2O2 upon B. cinerea infection. Overexpression of ClMBD1 and ClMBD2 led to down-regulated expression of AtPR1 and decreased resistance while overexpression of ClMBD5 resulted in up-regulated expression of AtPR1 and increased resistance against Pseudomonas syringae pv. tomato DC3000. Transcriptome analysis revealed that overexpression of ClMBD2 in Arabidopsis up-regulated the expression of a small set of genes that negatively regulate Arabidopsis immunity. These data suggest the importance of some ClMBD genes in plant immunity and provide the possibility to improve plant immunity through modification of specific ClMBD genes.